Religiosity and development: a look at political religiosity in fourth republic Nigeria and its effect on the nation’s development - Owoyemi, Musa Yusuf (2016)
As Nigeria successfully concluded another general election in 2015, religion once again played a divisive role in the nation political sphere as a Muslim presidential candidate from the north contested against a Christian presidential candidate from the south, thus separating the people along religious and ethnic lines. Based on this, this article examines the role of political religiosity in fourth republic Nigeria and how this has affected the nation in terms of development.Using the analytical method, this paper scans the pages of Nigerian newspapers in order to bring too light and explain how this political religiosity is another deception resorted to by the political class in order to fleece the nation and its people of its resources for their personal use and gains.Its findings revealed that the public display of religiosity by the political class in the fourth republic has led to a situation in which the people out of religious consideration have allowed politicians to continue the legacy of corruption, fraud, embezzlement and theft of the wealth of the nation passed down from the military era.